Multiple performance characteristics optimization for Al 7075 on electric discharge drilling by Taguchi grey relational theory - Rajesh Khanna; Anish Kumar; Mohinder Pal Garg; Ajit Singh; Neeraj Sharma (Journal of Industrial Engineering International, 2015)
Electric discharge drill machine (EDDM) is a spark erosion process to produce micro-holes in conductive materials. This process is widely used in aerospace, medical, dental and automobile industries. As for the performance evaluation of the electric discharge drilling machine, it is very necessary to study the process parameters of machine tool. In this research paper, a brass rod 2 mm diameter was selected as a tool electrode. The experiments generate output responses such as tool wear rate (TWR). The best parameters such as pulse on-time, pulse off-time and water pressure were studied for best machining characteristics. This investigation presents the use of Taguchi approach for better TWR in drilling of Al-7075. A plan of experiments, based on L27 Taguchi design method, was selected for drilling of material. Analysis of variance (ANOVA) shows the percentage contribution of the control factor in the machining of Al-7075 in EDDM. The optimal combination levels and the significant drilling parameters on TWR were obtained. The optimization results showed that the combination of maximum pulse on-time and minimum pulse off-time gives maximum MRR.
Keywords: 650; Electric discharge drilling machining; MRR; TWR; ANOVA; Taguchi method; Grey relational analysis